HTLV‐1 Tax‐specific memory cytotoxic T lymphocytes in long‐term survivors of aggressive‐type adult T‐cell leukemia/lymphoma - Tatsuro Jo; Kazuhiro Noguchi; Takahiro Sakai; Ritsuko Kubota‐Koketsu; Sadaharu Irie; Masatoshi Matsuo; Jun Taguchi; Kuniko Abe; Kazuto Shigematsu (Cancer Medicine, 2022)
Abstract Purpose Adult T‐cell leukemia/lymphoma (ATLL) is a relatively refractory peripheral T‐cell lymphoma caused by human T‐cell lymphotropic virus type 1 (HTLV‐1). The objective of this study was to investigate the characteristics of long‐term survivors with ATLL. Methods We conducted an observational study of 75 aggressive‐type ATLL patients. Flow cytometry was conducted to analyze HTLV‐1 Tax‐specific cytotoxic T‐lymphocytes (CTLs) and T‐cell receptor Vβ gene repertoire. Results We first evaluated six long‐term survivors among 37 patients who were newly diagnosed with ATLL and then treated with intensive chemotherapy without mogamulizumab, a monoclonal antibody for C‐C chemokine receptor four antigen. Reversal of the CD4‐to‐CD8 ratio (CD4/CD8) in peripheral mononuclear cells was observed in all six patients. Three of these six patients showed reversed CD4/CD8 immediately after herpes virus infection. Four of these six patients who could be examined demonstrated long‐term maintenance of HTLV‐1 Tax‐specific CTLs. We subsequently identified four long‐term survivors among 38 patients who were newly diagnosed with ATLL and then treated with intensive chemotherapy plus mogamulizumab. All four patients showed reversed CD4/CD8, and three of the four patients contracted herpes virus infection during immunochemotherapy. Six of the total 10 patients were subjected to CTL analyses. Tax‐specific CTLs were observed, and the CTLs that were almost entirely composed of memory CTLs in all patients were recorded. HTLV‐1 provirus was also detected in all six patients. Conclusions These data suggest that Tax‐specific memory CTLs probably, together with anticancer agents, eradicate ATLL cells and exhibit long‐term preventive effects from relapse ATLL. Thus, the strong activation of cellular immunity, such as herpes virus infection, seems to be necessary to induce such a potent number of Tax‐specific CTLs.